2020
DOI: 10.3390/ma13163617
|View full text |Cite
|
Sign up to set email alerts
|

Nano-Domains Produced through a Two-Step Poling Technique in Lithium Niobate on Insulators

Abstract: We proposed a two-step poling technique to fabricate nanoscale domains based on the anti-parallel polarization reversal effect in lithium niobate on insulator (LNOI). The anti-parallel polarization reversal is observed when lithium niobate thin film in LNOI is poled by applying a high voltage pulse through the conductive probe tip of atomic force microscope, which generates a donut-shaped domain structure with its domain polarization at the center being anti-parallel to the poling field. The donut-shaped domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…In the production environment, the calculation of the minimum polishing cycle time allowed to increase the processing efficiency by reducing the time of the polishing operation, reducing the number of polishing defects, and reducing the abrasive materials consumption. The presented results coincided with the authors’ conclusions [ 3 , 4 , 5 , 11 , 12 , 13 , 14 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In the production environment, the calculation of the minimum polishing cycle time allowed to increase the processing efficiency by reducing the time of the polishing operation, reducing the number of polishing defects, and reducing the abrasive materials consumption. The presented results coincided with the authors’ conclusions [ 3 , 4 , 5 , 11 , 12 , 13 , 14 ].…”
Section: Resultssupporting
confidence: 92%
“…The theory of the impact of free abrasive grains on the glass surface during its lapping is now generally accepted and has found its further development and refinement [ 6 , 8 , 9 , 10 , 11 , 12 , 13 ]. There are some differences in the operation of free and fixed abrasive grains which significantly influence the mechanism of action, the size of the deformed layer, and the micro relief of the processed surface [ 9 , 14 , 15 ]. In studies [ 1 , 9 , 10 , 16 ], it was found that the ratio of the depth F of the deformed and h of the relief layers for various grades of optical glass and minerals with a similar brittle criterion remains almost constant: F / h = K ≈ 4 ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The ways to pattern periodically switched domains in LiNbO 3 mainly include femtosecond laser writing [37] and high voltage-assisted domain switching [32,[38][39][40]. Although QPM was proposed early in 1962 [41], its practical feasibility was not proven until the 1980s.…”
Section: Periodic Polingmentioning
confidence: 99%